An Efficiency Rationale for Expenditure Equalization - Petchey, Jeffrey; Petchey, James (Centre for Research in Applied Economics, 2013)
This paper provides an efficiency rationale for expenditure equalization in federations. It does so by developing a fiscal federalism model with two citizen types; immobile non-workers and mobile workers. Three decision-makers, a federal transfer authority and two states, play a game as Nash competitors. In any Nash Equilibrium the federal authority chooses an efficient transfer that 'equalizes' for inter-state differences in state benefit and redistributive taxes as well as differences in per capita revenues (economic rents). Since state taxes are equal to per capita state expenditures on services this provides an efficiency rationale for expenditure equalization. Using examples it is shown that Australian equalization gets expenditure equalization in the 'right' direction from an efficiency perspective; from low to high cost states. This is not to say, however, that the magnitude of inter-state transfers induced by expenditure equalization in Australia is efficient.